Rapamycin rescues mitochondrial myopathy via coordinated activation of autophagy and lysosomal biogenesis - Gabriele Civiletto; Sukru Anil Dogan; Raffaele Cerutti; Gigliola Fagiolari; Maurizio Moggio; Costanza Lamperti; Cristiane Benincá; Carlo Viscomi; Massimo Zeviani (EMBO Molecular Medicine)
Abstract The mTOR inhibitor rapamycin ameliorates the clinical and biochemical phenotype of mouse, worm, and cellular models of mitochondrial disease, via an unclear mechanism. Here, we show that prolonged rapamycin treatment improved motor endurance, corrected morphological abnormalities of muscle, and increased cytochrome c oxidase (COX) activity of a muscle‐specific Cox15 knockout mouse (Cox15sm/sm). Rapamycin treatment restored autophagic flux, which was impaired in naïve Cox15sm/sm muscle, and reduced the number of damaged mitochondria, which accumulated in untreated Cox15sm/sm mice. Conversely, rilmenidine, an mTORC1‐independent autophagy inducer, was ineffective on the myopathic features of Cox15sm/sm animals. This stark difference supports the idea that inhibition of mTORC1 by rapamycin has a key role in the improvement of the mitochondrial function in Cox15sm/sm muscle. In contrast to rilmenidine, rapamycin treatment also activated lysosomal biogenesis in muscle. This effect was associated with increased nuclear localization of TFEB, a master regulator of lysosomal biogenesis, which is inhibited by mTORC1‐dependent phosphorylation. We propose that the coordinated activation of autophagic flux and lysosomal biogenesis contribute to the effective clearance of dysfunctional mitochondria by rapamycin.